Characterising and predicting bleeding in high-risk patients with an acute coronary syndrome. Issue 18 (24th June 2015) - Khan, Razi; Lopes, Renato D; Neely, Megan L; Stevens, Susanna R; Harrington, Robert A; Diaz, Rafael; Cools, Frank; Jansky, Petr; Montalescot, Gilles; Atar, Dan; Lopez-Sendon, Jose; Flather, Marcus; et al.
Abstract : Objective: In the Apixaban for Prevention of Acute Ischemic Events (APPRAISE-2) trial, the use of apixaban, when compared with placebo, in high-risk patients with a recent acute coronary syndrome (ACS) resulted in a significant increase in bleeding without a reduction in ischaemic events. The aim of this analysis was to provide further description of these bleeding events and to determine the baseline characteristics associated with bleeding in high-risk post-ACS patients. Methods: APPRAISE-2 was a multinational clinical trial including 7392 high-risk patients with a recent ACS randomised to apixaban (5 mg twice daily) or placebo. Bleeding including Thrombolysis in Myocardial Infarction (TIMI) major or minor bleeding, International Society on Thrombosis and Haemostasis (ISTH) major or clinically relevant non-major (CRNM) bleeding, and any bleeding were analysed using an on-treatment analysis. Kaplan–Meier curves were plotted to describe the timing of bleeding, and a Cox proportional hazards model was used to identify predictors of ISTH major or CRNM bleeding and any bleeding. Median follow-up was 241 days. Results: The proportion of patients who experienced TIMI major or minor, ISTH major or CRNM, and any bleeding was 1.5%, 2.2% and 13.3%, respectively. The incidence of bleeding was highest in the immediate post-ACS period (0.11 in the first 30 days vs 0.03 after 30 days events per 1 patient-year); however, >60% of major bleeding events occurred >30 days after the end of the index hospitalisation. Gastrointestinal bleeding was the most common cause of major bleeding, accounting for 45.9% of TIMI major or minor and 39.5% of ISTH major or CRNM bleeding events. Independent predictors of ISTH major or CRNM bleeding events included older age, renal dysfunction, dual oral antiplatelet therapy, smoking history, increased white cell count and coronary revascularisation. Conclusions: When compared with placebo, the use of apixaban is associated with an important short-term and long-term risk of bleeding in high-risk post-ACS patients, with gastrointestinal bleeding being the most common source of major bleeding. The baseline predictors of major bleeding appear to be consistent with those identified in lower-risk ACS populations with shorter-term follow-up. Clinical trial No: NCT00831441.